Out of Poverty : Comparative Poverty Reduction Strategies in Eastern and Southern Africa. - Kessy, Flora Lucas; Tostensen, Arne (Mkuki na Nyota Publishers, 2008)
This study examines, traces and maps the poverty reduction policies adopted by six countries in Eastern and Southern Africa since the mid-1990s with a view to highlighting differences and similarities.